Characteristics Study of Old Kampong Settlement in Batan Semarang City - Nurini, Nurini; Intan Kusumo Dewi, Diah; Kurniawati, Wakhidah; Zuleika Islamey, Talitha (Universitas Ibn Khaldun Bogor, 2022)
The development of urban areas occurs due to the demands for space for activities from the community. Increased activity in the city center has an impact on increasing the need for housing. Kampong Batan is one of the settlements located in the downtown triangle area of Pandanaran road, Pemuda road and Gajah Mada road (PANDAMA). Kampong Batan is also one of the old kampongs that experienced the growth of residential areas due to the development of activities. The implication of the development of activities in the city center to Kampong Batan is experiencing changes that are seen physically and non-physically. In this study, we will examine the characteristics of the Batan settlement in Semarang City in order to find out the changes that occur due to the development of activities in the city center. The research method used is field observation by looking at the development of Kampong Batan from the colonial era to the present based on the map of the previous year of Semarang City. Then it is identified the changes that occur based on the road network, changes in the use of residential space and the characteristics of the settlements. The result is that the settlement of Old Kampong Batan began to be filled with settlements from 1925 to 2000. The changes that are happening today can be seen from the expansion of residential activity space into a terrace, for parking and as a place to sell. In addition, many changes in the area that were previously only areas with residential functions have now turned into trade and service functions.